An investigation of cash holdings debt maturity and corporate performance considering managerial overconfidence evidence from listed Vietnamese firms - Dao, Thi Tuyet Nhung (2019)
One of the most important objectives of any firm is maximizing firm value. In order to achieve that goal, many different aspects come into play. One of those aspects is financial decisions. Financial decisions are mostly determined by managers, therefore, it can be stated that managers are people who play the main role in determining the success of firms. Stemming from this statement, this study attempts to investigate the impact of managerial overconfidence on some financial management aspects, including cash holdings, debt maturity and firm performance. Furthermore, the thesis also expands the research to examine the impact of managerial overconfidence on the deviation between the actual level of cash holdings and the optimal level of cash holdings, and the deviation between the actual level of debt maturity and the optimal level of debt maturity. By mainly focusing on data from 123 face-to-face interviews with top-line managers of Vietnamese non-financial listed firms, the thesis uses data on voice pitch to measure managerial overconfidence and test the effect of managerial overconfidence on the research topics. Besides using voice pitch, to strengthen the empirical results, the study also uses some other measurements of managerial overconfidence, including psychometric testing, bias in earnings forecast, manager’s gender, the visibility of CEOs’ photographs in firms’ annual reports and, a comprehensive index from multiple measurements of the research. The findings indicate that, firstly, firms with overconfident managers tend to hold less cash but the actual level of cash holdings is not far from the optimal level of cash holdings. Secondly, overconfident managers prefer using long-term debt over short-term debt, and they tend to make a higher deviation between the actual level of debt maturity and the target level of debt maturity. Finally, managerial overconfidence is found to be associated with a better result of firm performance.
Keywords: Business; Finance